Does a pint a day affect your child's pay? The effect of prenatal alcohol exposure on adult outcomes - Peter Nilsson (Centre for Microdata Methods and Practice (cemmap), 2008)
This paper utilizes a Swedish alcohol policy experiment conducted in the late 1960s to identify the impact of prenatal alcohol exposure on educational attainments and labor market outcomes. The experiment started in November 1967 and was prematurely discontinued in July 1968 due to a sharp increase in alcohol consumption in the experimental regions, particularly among youths. Using a difference-in-difference-indifferences estimation strategy we find that around the age of 30 the cohort in utero during the experiment has substantially reduced educational attainments, lower earnings and higher welfare dependency rates compared to the surrounding cohorts. The results indicate that investments in early-life health have far-reaching effects on economic outcomes in later life.
Keywords: I12; I18; J24; 330; infant health; education; earnings; alcohol policy; Alkoholkonsum; Gesundheit; Kinder; Bildungsniveau; Einkommen; Alkoholpolitik; Schätzung; Schweden